ASSESSMENT OF QUALITY OF LIFE IN ELDERLY PATIENTS WITH ISCHEMIC HEART DISEASE (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
To analyze the characteristics of clinical manifestations occurring against the background of combined cardiovascular and renal dysfunctions in elderly patients.